2021
DOI: 10.1111/hepr.13678
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based clinical practice guidelines for liver cirrhosis 2020

Abstract: The first edition of the clinical practice guidelines for liver cirrhosis was published in 2010, and the second edition was published in 2015 by the Japanese Society of Gastroenterology (JSGE). The revised third edition was recently published in 2020.This version has become a joint guideline by the JSGE and the Japanese Society of Hepatology (JSH). In addition to the clinical questions (CQs), background questions (BQs) are new items for basic clinical knowledge, and future research questions (FRQs) are newly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
171
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 217 publications
(308 reference statements)
0
171
0
1
Order By: Relevance
“…Therapeutic strategy for gastric variceal bleeding has not yet been established. Usefulness of endoscopic therapies and that of BRTO were shown in the clinical practice guideline for liver cirrhosis in Japan [ 14 , 15 ], while the indication of each therapy and the significance of combined BRTO plus endoscopic therapies were to be clarified in the future. Thus, at our institution, we undertake endoscopic therapies with or without BRTO for patients with gastric variceal bleeding, depending on the types and hemodynamics of the varices.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic strategy for gastric variceal bleeding has not yet been established. Usefulness of endoscopic therapies and that of BRTO were shown in the clinical practice guideline for liver cirrhosis in Japan [ 14 , 15 ], while the indication of each therapy and the significance of combined BRTO plus endoscopic therapies were to be clarified in the future. Thus, at our institution, we undertake endoscopic therapies with or without BRTO for patients with gastric variceal bleeding, depending on the types and hemodynamics of the varices.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians should be fully aware of these. In our ROC analysis, the AUC of SARC-F for the mild or more severe malnutrition and for the moderate or more severe malnutrition was higher than that of BMI, which is a good indicator of nutritional status [39]. The SARC-F score rather than BMI can be a good indicator for malnutrition.…”
Section: Discussionmentioning
confidence: 58%
“…HCC is well known to develop frequently in patients with chronic liver disease, who are often complicated with amino acid imbalance. Furthermore, it has been recommended that nutritional intervention be considered for cases of chronic liver disease with a serum albumin level ≤3.5 g/dL [39,40]. Additionally, it was recently reported that the borderline of amino acid imbalance shown by an ALBI score of −2.588 is similar to the cut-off value for ALBI grade 1 (−2.600) [9].…”
Section: Discussionmentioning
confidence: 99%